The Ready Made Garments (RMG) workers’ gender ratio in Bangladesh: the case of Mapped in Bangladesh (MiB) - Sadril Shajahan, MD.; Islam, Md. Faizul; Choudhury, Afshana; Ahmad, Faria; Chowdhury, Fahim S. (International journal of research in business and social science, 2021)
This article was published in the International Journal of Research in Business and Social Science [© 2021] and the definite version is available at : https://doi.org/10.20525/ijrbs.v10i7.1445. The Journal's website is at: http://www.hrpub.org/journals/article_info.php?aid=4083